Effects of Two Different Pozole Preparation Processes on Quality Variables and Pasting Properties of Processed Maize Grain - María Gricelda Vázquez-Carrillo; David Santiago-Ramos; Edith Domínguez-Rendón; Marco Antonio Audelo-Benites (Journal of Food Quality)
The effects of two different pozole preparation processes, traditional (TP) and industrial (IP), on quality variables, chemical composition, and pasting properties of processed grain of nine maize landraces were evaluated. Nixtamalization and steeping time in TP (~15 h) allowed more water absorption resulting in higher moisture content as well as softer debranned nixtamal relative to the debranned nixtamal produced by IP (52 min). Steeping in TP and bleaching in IP increased the pasting temperature, peak viscosity, and time to peak viscosity of maize starch. Flowering time was shorter in IP (<120 min) than in TP (>120 min) and was significantly affected by the hardness of debranned nixtamal and bleached precooked grains. Total dry matter loss was higher in IP (>10.5%) than in TP (<5.0%), mainly due to the complete elimination of pedicel and pericarp by the Ca(OH)2 + NaOH solution during cooking. Soft grains, with low test weight, a high proportion of floury endosperm, and high peak viscosity, are required to obtain higher yield of bleached precooked grains and soft flowered grains in both processes.